Risk of environmental transmission of norovirus infection from prior room occupants. (November 2021) - Fraenkel, C-J.; Böttiger, B.; Söderlund-Strand, A.; Inghammar, M.
Summary: Background: Environmental contamination of norovirus (NoV) is believed to be a significant source for further transmission in hospitals. Aim: To investigate the risk of acquiring NoV in a cleaned room previously occupied by a patient with NoV infection. The risk of having a roommate with recent NoV infection was also assessed. Methods: In a retrospective cohort, comprising 33, 788 room stays at five infectious Disease wards in southern Sweden from 2013 to 2018, the risk of acquiring NoV infection after admission to an exposed or non-exposed room was analysed with uni- and multivariable statistical analysis, controlling for age, colonization pressure and any roommate. RNA sequencing of the NoV strains involved in suspected room transmission was also performed. Results: Five of the 1106 patients exposed to a room with a prior occupant with NoV infection and 49 in the non-exposed group acquired NoV infection. An association between NoV acquisition was found in the univariable analysis (odds ratio (OR) 3.3, P =0.01), but not when adjusting for potential confounders (OR 1.9, P =0.2). Sequencing of the NoV samples showed that only two of the five exposed patients with acquired NoV infection were infected by identical strains to the prior room occupant, inferring a room transmission risk of 0.2% (95% confidence interval 0.05–0.78%). None of the 52 patients who shared room with a roommate with NoV symptoms resolved for ≥48 h acquired NoV infection. Conclusions: In absolute terms, the risk of room transmission of NoV is low. Discontinuation of isolation ≥48 h after resolution of symptoms seems adequate.